О биологической сущности резервуарного паразитизма и его значении в эволюции жизненных циклов гельминтов - Шарпило, В.П. (Вестник зоологии, 1979)
A conception is advanced and substantiated on duplicating systems appearing owing to participation of the reservoir hosts in helminths circulation. Successive stages of duplicating systems formation are considered. The main significance of the reservoir parasitism lies in existence of such systems.